Restorative Justice in Corporate Dispute Resolution as Business Actor in Indonesia - Abubakar, Lastuti; Afriana, Anita; Rajamanickam, Ramalinggam; Fakhirah, Efa Laela (Universitas Negeri Semarang, 2024)
Indonesian limited liability company (Perseroan Terbatas or